Enhanced stability and catalytic activity of bismuth nanoparticles by modified with porous silica. (November 2017) - Chen, Kejun; Fan, Wenjie; Huang, Caijin; Qiu, Xiaoqing
Abstract: The present work reports that the elemental bismuth nanoparticles (Bi NPs) modified with silica can be obtained via in-situ reduction of bismuth oxide nanoparticles with porous silica coating layers. The as-synthesized samples were characterized by the powder X-ray diffraction, scanning electron microscope, transmission electron microscope, the Brunauer-Emmett-Teller surface areas and X-ray photoelectron spectroscopy. It is found that metallic bismuth nanoparticles are well covered by porous silica (Bi@SiO2 ) to form hybrids. Coating metallic bismuth nanoparticles with permeable silica makes it unsusceptible to agglomeration and deactivation, even if the metallic Bi NPs are stored in the oxygen-rich and aqueous atmospheres. Moreover, the synthesized samples can be employed as catalyst for reduction of p-nitrophenol into p-aminophenol. The optimal catalyst of Bi@SiO2 -9.03 at% (9.03 = 100*nSi /nBi ) exerts more satisfactory catalytic property and outstanding reusability than the bare metallic bismuth in this target reaction. The superior stability and enhanced activity enable the practical application of Bi NPs to be available and expedient. Highlights: Bi@SiO2 composites were synthesized via in-situ reduction of Bi2 O3 @SiO2 . The thickness of silica coating in the composites can be precisely controlled to obtain optimal catalyst for reduction p-nitrophenol. The modified elemental bismuth nanoparticles delivered outstanding stability, catalytic activity and reusability.